Study of heart rate variability, metabolic markers and functional biomechanics parameters in basketball players submitted to ive loads periodization system - Mazon, J. H.; Souza, H. C. D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The aim of this study was to investigate if the application of selective loads periodization system (SLPS) promoted alterations in autonomic modulation of heart rate variability (HRV), functional biomechanics parameters, as well same metabolic markers in basketball players. Methods: Sixteen male basketball players were submitted to SLPS and evaluated before and after a preparatory period. The HRV was evaluated by a spectral analysis of R-R intervals in the supine position. The evaluation of metabolic markers consisted of measuring plasma catecholamines, cortisol, free testosterone, urea and creatine kinase. Functional biomechanical parameters were assessed through tests of strength (peak torque, maximal work) and power (countermovement jump - CMJ) of the lower limbs using isokinetic dynamometer and a force platform, respectively. Results: The results demonstrated that the training load used did not promote changes in the autonomic modulation of HRV. This affirmation is supported by the absence of change in oscillations of low frequency (LF), and high frequency (HF) of HRV. Regarding metabolic markers, we observed reductions in plasma dopamine and adrenaline, and increased plasma cortisol. Additionally, no significant differences in the parameters of strength and power were observed. Discussion: It is possible that the absence of change in LF and HF oscillations of HRV are associated with the fact that basketball is a predominantly anaerobic sport. The reduction in the levels of dopamine and adrenaline seem to reflect positive adjustments to the workloads during preparatory period since previous study reported an increase in the secretion of these hormones as a result of physiological stress in athletes during a competition period (Garatachea et al., 2012). In turn, the increased cortisol is still controversial, since the literature reports no consistent patterns for the training-induced adaptations in the basal concentrations of this hormone. However, we did not observe changes in testosterone/cortisol ratio, which is considered a potent endocrine biomarker of the anabolic-catabolic balance in athletes. Finally, the absence of changes in the strength and power parameters seem to be related to the applicability of tests in the verification the effectiveness of training, since the maximum expression of these capacities hardly occurs during play.